Comparing teaching examples: effects on the solution quality and learning outcomes of student teachers’ professional vision of classroom management - Wedde, Sonja; Busse, Annette; Bosse, Dorit; Gold, Bernadette (Frontiers in Education, 2023)
Young teachers, in particular, often face difficulties in managing their classrooms. A professional vision of classroom management can support teachers in managing a classroom effectively. This element of professional competence is often promoted in teacher training using video-based approaches, e.g., videoing own lessons including expert feedback, analyzing instructional videos and accompanying transcripts and analyzing videos of own and others teaching. This study used the learning format of comparing contrasting cases to promote professional vision of classroom management among first-semester student teachers (N = 127). However, it diverged slightly from the norm in that its contrasting cases came from two auditive, not video, teaching examples. The effectiveness of comparing contrasting cases on the professional vision of classroom management was studied in two experimental groups. One group compared the contrasting cases using self-generated categories (invention activity, n = 63), and the other group compared the cases based on given categories (worked solution, n = 64). Professional vision of classroom management was assessed using a video-based online test in a pre-post design to determine whether it was more beneficial to compare contrasting cases with an invention activity or a worked solution. Additionally, using a coding scheme, we assessed the quality of the student teachers’ task solutions and the relationship between the quality of the task solutions and the learning outcomes of the posttest. Both groups showed no difference between the benefits of the two learning formats. For the experimental group invention activity, we found negative correlations between the task solutions and the learning outcomes. We ascribe this correlation to a productive failure effect. We performed a second study (N = 54) with a follow-up test to investigate whether either of the two formats produced more sustainable results. Our studies showed that both experimental groups (invention activity: n = 24, worked solution: n = 30) also had a short-term increase in professional vision of classroom management. The invention activity, however, promoted the more sustainable acquisition of professional vision of classroom management. In conclusion, invention activities appear to be an appropriate task format for promoting professional vision of classroom management among student teachers.